2013
DOI: 10.1177/0091270012440282
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Human Pharmacokinetic Prediction Based on In Vivo Animal Pharmacokinetic Data, Part 2: Clearance

Abstract: A comprehensive analysis on the prediction of human clearance based on intravenous pharmacokinetic data from rat, dog, and monkey for approximately 400 compounds was undertaken. This data set has been carefully compiled from literature reports and expanded with some in-house determinations for plasma protein binding and rat clearance. To the authors- knowledge, this is the largest publicly available data set. The present examination offers a comparison of 37 different methods for prediction of human clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 36 publications
1
75
0
Order By: Relevance
“…6) and the published MLR model (Eq. 7), the values of geometric meanfold error (GMFE) and bias 36 were calculated for both models. These model predictivity metrics are listed in Table 6.…”
Section: Validation On External Data Setsmentioning
confidence: 99%
“…6) and the published MLR model (Eq. 7), the values of geometric meanfold error (GMFE) and bias 36 were calculated for both models. These model predictivity metrics are listed in Table 6.…”
Section: Validation On External Data Setsmentioning
confidence: 99%
“…Compound selection was based on previous literature studies indicating intestinal metabolism. The human bioavailability databases published by Lombardo et al (2013) , Musther et al (2014) , Bueters et al (2013) and Varma et al (2010) were used for this purpose. An inclusion criterion in this study was the availability of i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Because other studies have shown that increasing the number of descriptors does not necessarily increase the predictive power from descriptor to PK properties [ 47 , 57 ], and to limit descriptors to those that are easily accessible to the public, no additional descriptors were calculated for this study.…”
Section: Methodsmentioning
confidence: 99%